Physiological testosterone replacement effects on male aged rats with orchiectomy-induced osteoporosis in advanced stage: a tomographic and biomechanical pilot study - de Paiva Gonçalves, Vinícius [UNESP]; Cabrera-Ortega, Adriana Alicia; Carvalho, Jhonatan de Souza [UNESP]; Ramadan, Dania [UNESP]; Spolidorio, Luís Carlos [UNESP] (Taylor & Francis, 2021)
Aim: This study aimed to evaluate the effect of physiological testosterone replacement on male aged rats with orchiectomy-induced osteoporosis in advanced stage. Methods: Thirty male rats (Rattus norvegicus albinus, Holtzman lineage) were randomly distributed into 3 groups (n = 10): 1-sham, 2-orchiectomy (OCX), 3-OCX + testosterone replacement (OCX + T). On day 0, a sham or orchiectomy surgery was performed according to the groups. Thirty and sixty days after surgeries, the animals from OCX + T group received testosterone intramuscularly, and the rats in all groups were euthanized on day 77. The femurs were removed for micro-CT scanning and biomechanical test. Results: Orchiectomy resulted in a marked trabecular bone damage (p < 0.05), which was not reversed with testosterone treatment (OCX + T group). The femoral strength was lower in orchiectomized animals (p < 0.05), while the bone strength in OCX + T group was similar to that observed in the sham animals (p > 0.05) and correlated to this parameter the deformation of rupture was smaller in OCX + T group. Conclusion: In conclusion, testosterone depletion induced by orchiectomy established an osteoporotic environment, mainly affecting the trabecular bone. Moreover, even though testosterone treatment did not enhance these variables, the hormonal replacement improved the femoral fracture strength and promoted beneficial effects on the biomechanical parameters compromised by castration in femoral bone.
Keywords: femoral fractures; hypogonadism; Male; osteoporosis; testosterone